(untitled) (Derna Academy Journal for Applied Sciences, 2025)
Olive mill wastewater (OMWW) poses a serious environmental concern due to its high organic load, elevated salinity, phenolic content, and dense microbial population, making conventional treatment processes both expensive and technically demanding, particularly in rural regions. This study aimed to assess the effectiveness of a natural, multi-layered filtration system composed of locally sourced materials—sand, activated carbon, and halophyte species such as Posidonia oceanica and Neptune balls—in enhancing OMWW quality. Two prototypes were designed and evaluated: an initial experimental filter and an optimized final model with refined material thicknesses and distributions to minimize clogging and maximize efficiency. The final filter showed notable pollutant removal performance, reducing chemical oxygen demand (COD) by 95–96%, biological oxygen demand over 5 days (BOD₅) by 61–90.8%, and total phenolic compounds by 94–95%. Microbial contamination was significantly reduced, with an 80–94% decrease in total colony count and complete elimination (100%) of fecal coliforms. Additional improvements were observed in color, turbidity, and odor of the treated effluent. The use of abundant natural materials suggests a practical and sustainable approach to OMWW treatment, particularly in decentralized rural settings where industrial solutions are not feasible. These findings highlight the potential of this method for mitigating the environmental burden of OMWW, supporting its safe discharge or reuse in agriculture, and contributing to long-term water resource conservation and ecological sustainability.